FIRST EXPERIENCE OF BOSENTAN IN COMPLEX MANAGEMENT OF A CHILD WITH VENA GALENI ANEURYSM - I. I. Trunina; A. S. Sharykin; M. I. Livshits; T. R. Lavrova; I. M. Osmanov (Российский кардиологический журнал, 2017)
During postnatal period, the causes of progressing heart failure are not only the inborn defects or cardiac rhythm disorders, but extracardiac diseases as well. Among such pathologies are the arterial-venous malformations of the brain vessels, including vena Galeni aneurysm. Inside the aneurysmatic sacks of the brain vessels, up to 80% of blood ejected from the left ventricle could be shunted, which leads then through the right chambers and causes heart failure and pulmonary hypertension. Recent drug treatment makes it to effectively treat pulmonary hypertension, compensate the signs of heart failure and stabilize the condition of a newborn before surgery. The case presented, is a bright evidence of this.